2021
DOI: 10.1161/atvbaha.120.315737
|View full text |Cite
|
Sign up to set email alerts
|

Statin Effects on Vascular Calcification

Abstract: Objective: Statins lower cardiovascular event risk, yet, they paradoxically increase coronary artery calcification, a marker consistently associated with increased cardiovascular risks. As calcium deposits influence rupture risk due to stress from compliance mismatch at their surfaces, we hypothesized that statins may lower cardiovascular risk by altering the microarchitecture of calcium deposits. Thus, using mice with preexisting vascular calcification, we tested whether pravastatin reduces the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“…22 Xian et al examined the effect of statin use on mice and found that pravastatin use may alter the progression and microarchitectural features of vascular calcium deposits. 23 Nevertheless, our study cannot determine the cause–effect relationship as to whether statin use elevated the CAC or CAC as a direct or indirect cause for statin use.…”
Section: Discussionmentioning
confidence: 83%
“…22 Xian et al examined the effect of statin use on mice and found that pravastatin use may alter the progression and microarchitectural features of vascular calcium deposits. 23 Nevertheless, our study cannot determine the cause–effect relationship as to whether statin use elevated the CAC or CAC as a direct or indirect cause for statin use.…”
Section: Discussionmentioning
confidence: 83%
“…245 There is also a study reported that pravastatin can alter the microarchitecture of aortic calcium deposits to protect against VC. 246 Clinical studies also show disparate results. The PARADIGM Study sought to elucidate the effect of statins on coronary atherosclerotic plaques.…”
Section: Statins and Vcmentioning
confidence: 99%
“…There is study found that statins are capable of promoting atherosclerotic calcification through the disinhibition of a macrophage Rac1‐IL‐1β signaling axis 245 . There is also a study reported that pravastatin can alter the microarchitecture of aortic calcium deposits to protect against VC 246 . Clinical studies also show disparate results.…”
Section: Potential Therapeutic Strategies Of Vcmentioning
confidence: 99%
“…Vascular calcification accompanies aging and atherosclerosis, but hitherto, it has not been a direct therapeutic target [ 178 ]. In this context, ECM-focused therapies may be explored to expand ongoing efforts limited to skin aging [ 179 ].…”
Section: Perspectivesmentioning
confidence: 99%